Dahir of May 16, 1930 AD - Ma’rib’s exterior and internal contradictions (Journal of Human Sciences, 2024)
In this research, we present and discuss a very sensitive issue, given its connection to the conscience of the Moroccan nation. Although it is one of the effects of French protectionism, it has been transferred to the collective memory, which is already burdened with historical accumulations that were revealed by the deed created by the colonizer when issuing the Decree of 5/16/1930 AD, which revealed responses and interactions. The Moroccans faced with him and with him a problem related to identity and citizenship, but its effects are still valid and renewed, and reproduce themselves, albeit in the form of dialogues and debates between Moroccan elites and intellectuals. The view of the supporters of the national movement on the event is still the same as the view of their predecessors, while the defenses and orientations of the advocates of the Amazigh language and those carrying its legacy appear to be Linguistic, cultural, historical, and even ethnic, they are more ferocious and determined to lift the state of oppression they believe.